Comparison of Oncology Patients' and Their Family Caregivers' Attitudes and Concerns Toward Pain and Pain Management. Issue 4 (July 2016) - Valeberg, Berit Taraldsen; Miaskowski, Christine; Paul, Steven M.; Rustøen, Tone
Abstract : Background: Both cancer patients and their family caregivers (FCs) report concerns about pain and pain management. When dyads share appraisal of the illness context, they may experience better dyadic adjustment. Objective: The aim of this study was to compare oncology outpatients' and their FCs' attitudes and concerns toward pain and pain management. Methods: In a cross-sectional study, outpatients with pain (n = 71) and their FCs completed the Barriers Questionnaire II, the Brief Pain Inventory, and information about demographic characteristics. Correlations and paired-samples t tests were calculated to evaluate agreement and differences in barrier scores between the patients and their FCs. Results: Congruence was found in patients' and FCs' beliefs about pain and the use of analgesics on 4 of 7 subscales (ie, tolerance, immune system, side effects, distract the medical doctor) and on the Barriers Questionnaire II total score. Both patients and their FCs were most concerned about addiction. Conclusions: The concerns that both patients and their FCs have about pain and the use of analgesics may act as barriers to effective pain management. Fear of addiction may be an important barrier to cancer pain management. Only small differences were found in concerns between the patients and their FCs. Implications for Practice: Patients and FCs need education about perceived barriers to effective pain management. They should be coached together to maintain or increase the congruence between them.